Development of Agritourism in the Light of Economics: Case Studies of Italy and Poland - Harshavardhan Kummitha; Raqif Huseynov; Michał Wojtaszek (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
Recreational activities pertaining to farmlands are receiving increased attention from both research and practice. One of the major reasons for this heightened importance attributed to farmland tourism is due partly to its potential to advance the local economy and to the benefits it brings for farmers and visitors. Thus, analyzing the role of agritourism in advancing socio-economic prosperity is of pivotal importance. With this background, the paper discusses the economic benefits of agritourism. The results reported in the paper are related to organizations located in Poland and Italy. Agritourism can bring several economic benefits in the countries and regions. What is interesting, the average income from agritourism is about one-third of the overall household income of farmers. Moreover, food service is a crucial factor in the success of agritourism as it brings extra money to farmers. It shows the importance of the relationship between the income obtained from agritourism activities and the benefits local communities gain by engaging in multiple tourism promotion activities.